2021
DOI: 10.3390/foods10020315
|View full text |Cite
|
Sign up to set email alerts
|

Perilla frutescens Leaf Extract and Fractions: Polyphenol Composition, Antioxidant, Enzymes (α-Glucosidase, Acetylcholinesterase, and Tyrosinase) Inhibitory, Anticancer, and Antidiabetic Activities

Abstract: This study aims to evaluate the bioactive components, in vitro bioactivities, and in vivo hypoglycemic effect of P. frutescens leaf, which is a traditional medicine-food homology plant. P. frutescens methanol crude extract and its fractions (petroleum ether, chloroform, ethyl acetate, n-butanol fractions, and aqueous phase residue) were prepared by ultrasound-enzyme assisted extraction and liquid–liquid extraction. Among the samples, the ethyl acetate fraction possessed the high total phenolic (440.48 μg GAE/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 53 publications
2
33
1
Order By: Relevance
“…Indeed, among ten accessions of P. frutescens Ahmed and Tavaszi-Sarosi [7] detected a total polyphenol content between 137.5 and 234.2 mg GAE/g DW, while Radacsi et al [27] found values between 84.7 and 204.3 mg GAE/g DW in leaves of five different accessions of P. frutescens analyzing them in two consecutive years. Additionally, recent publications have indicated values around 200 mg GAE/g DW for both varieties (green and red) of P. frutescens [28] and even values of more than 400 mg GAE/g DW in leaves of an unspecified Chinese basil variety [29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, among ten accessions of P. frutescens Ahmed and Tavaszi-Sarosi [7] detected a total polyphenol content between 137.5 and 234.2 mg GAE/g DW, while Radacsi et al [27] found values between 84.7 and 204.3 mg GAE/g DW in leaves of five different accessions of P. frutescens analyzing them in two consecutive years. Additionally, recent publications have indicated values around 200 mg GAE/g DW for both varieties (green and red) of P. frutescens [28] and even values of more than 400 mg GAE/g DW in leaves of an unspecified Chinese basil variety [29].…”
Section: Discussionmentioning
confidence: 96%
“…According to the correlation between the level of phenolic compounds and antioxidant capacity [32], the low TPC content is probably the reason for the low levels of antioxidant capacity which can hardly be directly compared with other authors due to the lack of uniformity in the unit of measurement used to express the data, e.g., for the DPPH assay, from % [28] down to µg of Trolox/mg DW [29] or the IC 50 [33].…”
Section: Discussionmentioning
confidence: 97%
“…In a recent animal study, polyphenols-rich Perilla frutescens leaf extracts (250 mg/kg body weight (bw)) were orally administrated to high-fat-diet-fed rats for 4 weeks. The results revealed that Perilla frutescens significantly reduced the plasma LDL-C level by 53% (p < 0.05) [78]. In an animal model study conducted by Li and colleagues revealed that the decrease of the plasma LDL-C content by 45% in the onion-fed group was associated with the inhibition of HMGR and the upregulation of LDLR expression, which was a plausible mechanism for its LDL-C lowering effect.…”
Section: Dietary Polyphenols: Potential Ldl-c Lowering Agentsmentioning
confidence: 90%
“…In another study conducted by Sarikurkcu et al [50], the MeOH extract of O. ambigens exhibited higher tyrosinase inhibitory activity than other extracts and was rich in apigenin 7-glucoside and luteolin 7-glucoside. ere are also some reports in the literature that plant extracts rich in rosmarinic acid [61][62][63], vanillic acid [64,65], and pinoresinol [66] show significant tyrosinase inhibitory activity.…”
Section: Discussionmentioning
confidence: 97%